The Pros and Cons of Determining National Disaster Status for The Sumatra Floods: Legal and Social Perspectives - Muis; Rabith Madah Khulaili Harsya; Liestyowati; Andi Lulu Isvany; Ainun Nazriah (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
The determination of national disaster status in Indonesia is often the subject of heated debate between humanitarian urgency and considerations of economic and political stability. This article analyzes the pros and cons of declaring a national disaster status in response to flooding on Sumatra Island through legal and social perspectives. Using qualitative methods with a juridical-normative and sociological approach, this study evaluates the implementation of Law Number 24 of 2007 concerning Disaster Management. The research findings indicate that legally, the determination of national disaster status provides unlimited access to fiscal resources and centralized command, but socially, it can create regional dependency and stigmatization, impacting the investment climate. This article concludes that more rigid quantitative indicators are needed in regulations to minimize the politicization of disaster status.